The utility of injury narratives for prioritising future prevention activities in small and medium enterprises in rural Vietnam. Issue 2 (2nd June 2012) - Marucci-Wellman, Helen; Willetts, Joanna L; Diep, Nguyen Bich; Binh, Ta Thi Tuyet
Abstract : Objectives: Injuries are a leading cause of work-related disability and death in rapidly developing countries such as Vietnam. The authors' objective was to demonstrate the utility of detailed injury narratives, derived from a household survey, in providing information on the determinants of work-related injuries to inform potential intervention targets. Methods: In a cross-sectional survey administered to 2615 households of a rapidly developing community of Vietnam where many workers engage in both agriculture and industrial work, the authors collected information about self-reported work-related injuries, annual hours worked in each industry and narrative text describing the circumstances of each injury. The authors used a customised coding taxonomy to describe injury scenarios. Results: Several intervention themes emerged, including the implementation of machine guarding, the use of cut resistant gloves and safety glasses which would benefit the small- and medium-sized enterprises. Calculation of incidence rates using full-time equivalents, stratified by work group, provided some unexpected observations of the risks of working in agriculture; workers who work in agriculture in addition to another industry are at an increased risk of fatigue or overexertion and other consequences of working too hard in their agricultural activities. Conclusions: A lack of aggregate injury statistics makes it difficult for the owners of small- and medium-sized enterprises to recognise a priori the most effective safety interventions. This analysis of detailed injury narratives with an appropriate taxonomic basis offers the ability to focus on the level of cause, activity and source and may inform the choice of various potential interventions at the workplace or enterprise level.